Reducing Information Asymmetry with ICT: A critical review of loan price and quantity effects in Africa - Simplice Asongu; Sara Le Roux (African Governance and Development Institute (AGDI), 2016)
This study investigates loan price and quantity effects of information sharing offices with ICT, in a panel of 162 banks consisting of 42 African countries for the period 2001-2011.The empirical evidence is based on Generalised Method of Moments and Instrumental Quantile Regressions. Our findings broadly show that ICT with public credit registries decrease the price of loans and increase the quantity of loans. While the net effects from the interaction of ICT with private credit bureaus do not lead to enhanced financial access, corresponding marginal effects show that ICT can complement private credit bureaus to increase loan quantity and decrease loan prices when certain thresholds of ICT are attained. We compute and discuss the ICT thresholds that are required to make this possible.
Keywords: G20; G29; L96; O40; O55; 330; Financial access; Information asymmetry; ICT